Kashrut in hospital (1817-1919) - Porro, Alessandro; Iannotti, Deborah Sabrina; Auxilia, Francesco; Castaldi, Silvana; Piga, Maria Antonella; Falconi, Bruno; Franchini, Antonia Francesca (Medicina Historica, 2022)
How guaranteed is the adherence to kasherut for the provision of meals to Jewish patients in our hospitals? In the city of Milan an experiment was conducted in 2000 at the San Carlo Borromeo Hospital and an agreement between the Lombardy Region and the Milan Jewish Community was drawn up in 2009. Was this problem addressed in the past? If so, what were the characteristics of the service? We can try to delimit the field of our analysis and define a time frame between two major war events: the Napoleonic wars and the First World War. We propose some experiences in the cities of Venice and Trieste. The current situation does not differ much from that of the 19th century. For the 19th century, the solutions adopted intervened in a context in which the respect for rights in generalist institutions was anything, but a given. The cited cases of Trieste and Venice represented models of reference and proposed themselves as advanced solutions for the protection of rights in the hospital and healthcare sector. However, their closure was influenced by economic sustainability, which even today affects health (and hospital) organisation and management. On the other hand, from the point of view of medical museology, the Venetian case reminds us that places can be integrated into routes for the enjoyment of medical historical cultural heritage. In fact, the area of the Israelitic Ward can be identified and could be reconverted to complete a Jewish Medicine Route within the Venetian hospital.